Brand communication of Russian state corporations: conceptual approaches and current state - D. Yu. Faikov; S. D. Faikova (Вестник университета)
Unfriendly actions against Russia taken by the “global North” predetermine the need not only to strengthen defense capability and economic sovereignty, but also to expand international cooperation with other states. Strong brands of state-owned corporations, which have well-known successes at the global level, may help solve these problems. The purposes of the article are to formulate conceptual goals of branding of scientific and industrial state corporations and to assess their existing brand communications. Based on theoretical and legal analysis, it has been determined that such goals should be the following: the creation and maintenance of a strong corporate brand, the brand of a responsible employer, the brand of Russia as a high-tech country with advanced science and education that cares for the development of the population and territories. These brands should form the citizens’ confidence in strength of the state, patriotism. Empirical and content analysis has shown that state corporations, such as “Rosatom”, “Rostec”, “Roscosmos”, create systems of brand communications aimed at forming strong corporate brands and a positive image of the state. They include a wide range of contacts with audiences. Certain differences in brand communications have been identified for each state corporation related to the accents of missions and target audiences. It has been concluded that there is a need for a deeper assessment of the effectiveness of branding.